Management Towards Sustainable Tourism Development for the Elderly in Lat Krabang District - โตสัจจะวงษ์, จรูญวิทย์; จิรอุดมสาโรจน์ , พัทธ์ธีรา; เสนีชัย , อัศวิน; โพธิ์เกษม, ภนิดา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aims to examine the factors influencing the satisfaction of elderly people in tourism, focusing on five independent variables: accessibility and convenience, safety care, facilities and services, community involvement and activities, and access to information and services, in relation to elderly tourists' satisfaction. The data analysis employed Multiple Regression Analysis, collecting data from 300 elderly people with tourism experience. The findings revealed that facilities and services had the highest impact on satisfaction (β = 0.35, p-value = 0.005), followed by accessibility and convenience (β = 0.32, p-value = 0.01), and safety care (β = 0.28, p-value = 0.03). Meanwhile, community involvement and activities, as well as access to information and services, also had statistically significant effects. These results indicate that tourism destinations suitable for the elderly should provide convenient and safe travel facilities, clear information, and easily accessible activities to enhance their tourism experience. These findings can serve as guidelines for developing tourist destinations that effectively and sustainably meet the needs of elderly tourists.